PAMAM-Calix-Dendrimers: Second Generation Synthesis, Fluorescent Properties and Catecholamines Binding - Olga Mostovaya; Igor Shiabiev; Dmitry Pysin; Alesia Stanavaya; Viktar Abashkin; Dzmitry Shcharbin; Pavel Padnya; Ivan Stoikov (MDPI AG, 2022)
A convenient method for the synthesis of the second generation of PAMAM dendrimers based on a p-tert-butylthiacalix[4]arene core in cone, partial cone and 1,3-alternate conformations was developed. Unusual fluorescence of the obtained PAMAM-calix-dendrimers has been found and explained. The binding ability of the synthesized dendrimers toward catecholamines (dopamine, L-adrenaline and L-noradrenaline) was shown by UV-Vis, fluorescence, 1D and 2D NMR spectroscopy and the binding constants (logKa 3.85-4.74) calculated. As was shown, the PAMAM-calix-dendrimers bind catecholamines by the internal cavities. All the studied hormones were most efficiently bound by the dendrimers bearing a macrocyclic core in 1,3-alternate conformation. The size of the formed supramolecular systems of dendrimer/catecholamine was established by the DLS method. A decrease in hemolytic activity of the PAMAM-calix-dendrimers with an increase in the generation number of a dendrimer was shown for the dendrimers with a core in 1,3-alternate conformation. The prospects for the use of the synthesized dendrimers with the macrocyclic core as drug delivery agents were discussed.